STUDENT LOANS IN THE SCALE OF SHARI’AH - Sackor, Muhammed (Antis-Publisher, 2025)
Objective: This study investigates the socio-economic challenges faced by Muslim families in the U.S. due to the interest-based student loan system, which conflicts with Islamic principles that explicitly prohibit riba (interest). Method: A comprehensive analysis of the student loan crisis in the U.S. is conducted, incorporating recent data and examining contemporary Islamic scholarly views on the permissibility of student loans. Results: The findings reveal that the existing student loan system imposes significant financial burdens on Muslim families and graduates, highlighting the growing dilemma of balancing religious principles with educational and economic needs. The paper also identifies alternative financial models that align with Islamic teachings. Novelty: This research contributes to the ongoing discourse on Islamic finance by providing a critical examination of the student loan system in the U.S. through the lens of Islamic law, offering practical recommendations for Muslim communities to address this issue in the future.